Effectiveness of metaverse-based nursing education on operating room patient safety - Jieun Shin; Nam-Yi Kim (PLoS ONE, 2025)
Purpose It is speculated that practical education that utilizes the metaverse can reduce the drawbacks of limited practice environments for nursing students and achieve the educational goals of clinical practice to improve the competency and academic satisfaction of nursing students. Metaverse can represent the actual clinical experience and participation of learners. This study aimed to develop metaverse-based nursing education content on operating room patient safety and verify its effects on nursing students’ learning transfer motivation, self-regulated learning, self-efficacy, and patient safety nursing. Methods This study had a nonequivalent control group pre- and post-experimental design. Nursing education content was developed based on the ASSURE model. The content consisted of surgical hand washing, sterile gown wearing, patient confirmation, surgical counting, specimen management, and high-risk drug management. The control group underwent clinical training in the operating room, and the experimental group underwent practical training in the metaverse operating room. Results The control and experimental groups included 19 and 25 participants, respectively. On comparing the study variables after the intervention, the difference between the control and experimental groups was not statistically significant, and the average score of the experimental group was generally higher. In particular, patient safety nursing scores improved from 3.99 to 4.79 in the control group and from 4.05 to 4.80 in the experimental group. Both groups showed significant improvement from pre- to post-intervention, with similar trends in educational outcomes observed across the two groups. Conclusion Both training methods demonstrated comparable educational outcomes. These findings suggest that metaverse-based education has the potential to be a viable alternative to traditional clinical training in operating room patient safety nursing.